2019
DOI: 10.3892/etm.2019.7324
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol downregulates the TLR4 signaling pathway to reduce brain damage in a rat model of focal cerebral ischemia

Abstract: Previous studies have demonstrated that inflammation and disruption of the blood-brain barrier (BBB) are important pathological processes during focal cerebral ischemia. Therefore, the present study evaluated the neuroprotective effects of resveratrol against brain damage, inflammation and BBB disruption in rats with focal cerebral ischemia and assessed the potential underlying molecular mechanisms. Sprague-Dawley rats underwent cerebral ischemia/reperfusion (IR) and then received intraperitoneal resveratrol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Sequence pairing analysis showed that lncRNA H19 and TLR4 shared common binding loci on the miR-17 sequence, and DLR assay confirmed that lncRNA H19 and TLR4 could bind to TLR4 is an important member of cellular immunity and mediates the release of proinflammatory factors, 26 and its abnormal expression may trigger a series of diseases or cancers. [27][28][29][30] In the case of adenomyosis, the inflammatory response induced by TLR4 promotes the excessive proliferation of ESCs and endows them with invasive phenotypes, 31 resulting in the cells to invade to myometrium. According to our findings, LVG reduces the level of TLR4 in ESCs by regulating lncRNA H19/miR-17, thus attenuating the inflammatory response (down-regulation of TNF-α, IL-6, IL-8, IL-17 and IL-1β), and finally suppressing the excessive proliferation and malignant proliferation of ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence pairing analysis showed that lncRNA H19 and TLR4 shared common binding loci on the miR-17 sequence, and DLR assay confirmed that lncRNA H19 and TLR4 could bind to TLR4 is an important member of cellular immunity and mediates the release of proinflammatory factors, 26 and its abnormal expression may trigger a series of diseases or cancers. [27][28][29][30] In the case of adenomyosis, the inflammatory response induced by TLR4 promotes the excessive proliferation of ESCs and endows them with invasive phenotypes, 31 resulting in the cells to invade to myometrium. According to our findings, LVG reduces the level of TLR4 in ESCs by regulating lncRNA H19/miR-17, thus attenuating the inflammatory response (down-regulation of TNF-α, IL-6, IL-8, IL-17 and IL-1β), and finally suppressing the excessive proliferation and malignant proliferation of ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, accumulating evidence indicated that RES treatment exerted neuroprotection against various brain disorders [ 247 , 248 , 249 ], including neurodegenerative diseases [ 250 , 251 , 252 ] such as Parkinson’s, Alzheimer’s, and Huntington’s diseases [ 253 , 254 ]. In addition, resveratrol also has neuroprotective effects in animal models of stroke [ 255 ], traumatic brain injury [ 256 ], and various kinds of ischemic brain injury ischemia [ 257 , 258 ] such as focal cerebral ischemia [ 259 , 260 , 261 ], global cerebral ischemia [ 262 , 263 ], and ischemia/reperfusion [ 264 , 265 , 266 , 267 ]. The RES mechanisms of action in neuroprotection might comprise antioxidation [ 268 , 269 ], anti-inflammation [ 270 , 271 ], and anti-apoptosis [ 272 ] effects.…”
Section: Pharmacological Evidence Of Natural Plant Products In Neomentioning
confidence: 99%
“…A previous study described that resveratrol has reduced infarction volume and brain water content (Dong et al, 2008). This was achieved due to the antioxidative property of resveratrol (Lei, Tu, Wang, Tu, & Shi, 2019). N‐acetyl cysteine (NAC) was also used as a ROS inhibitor for in vitro studies.…”
Section: Introductionmentioning
confidence: 99%